2005
DOI: 10.1039/b409577d
|View full text |Cite
|
Sign up to set email alerts
|

One-year monitoring survey of organic compounds (PAHs, PCBs, TBT), heavy metals and biomarkers in blue mussels from the Arcachon Bay, France

Abstract: Marine mussels Mytilus sp. were transplanted on a monthly basis in cages over one year to oyster farms and harbours in the Arcachon Bay (France) in order to assess the water quality of the bay. Contaminant levels (organotin compounds, trace metals, PCBs and PAHs) were measured in tissues of transplanted mussels and mussels from a reference station, along with physiological parameters of the mussels (condition indexes, lipid content and dry weight). Four biomarkers (AChE: acetylcholinesterase activity, GST: glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 59 publications
(64 reference statements)
6
41
1
1
Order By: Relevance
“…In this way, they are capable of resisting high levels of chemical contamination and of bioconcentrating xenobiotics to more than a thousand times background levels, which can facilitate chemical analysis. The usefulness of mussels as bioindicators is greatly increased when chemical analyses are integrated with data on the biological effects of pollutants (Bayne et al 1988;Cajaraville et al 2000;Devier et al 2005). In this context, both laboratory and field studies have demonstrated that different biochemical, cellular and physiological indexes may be useful in marine organisms as biomarkers of exposure or damage due to chemical pollution (Lam and Gray 2003).…”
Section: Introductionmentioning
confidence: 98%
“…In this way, they are capable of resisting high levels of chemical contamination and of bioconcentrating xenobiotics to more than a thousand times background levels, which can facilitate chemical analysis. The usefulness of mussels as bioindicators is greatly increased when chemical analyses are integrated with data on the biological effects of pollutants (Bayne et al 1988;Cajaraville et al 2000;Devier et al 2005). In this context, both laboratory and field studies have demonstrated that different biochemical, cellular and physiological indexes may be useful in marine organisms as biomarkers of exposure or damage due to chemical pollution (Lam and Gray 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Bivalves are suitable organisms for biomonitoring toxic elements and chemical compounds in the marine environment. Among them mussels have been intensively investigated from the ecotoxicological points of view as well as food safety, since they exhibit high potential for biomonitoring and represent one of the important seafood products for human consumption (Rivaro et al, 1997;Da Ros, 2000;Gallina et al, 2000;Chase et al, 2001;Besada et al, 2002;Adami et al, 2002;Szefer et al, 2004;Devier et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The RPAH level in this study was far higher than that in rice (mean value: 2.19 ng/g fresh weight) collected from local markets of Catalonia, Spain (Perelló et al 2009), over 2 times higher than that in hull (95.7 ng/g dry weight) collected from a paddy field in Tianjin, one of the most heavily contaminated areas with PAHs in China (Tao et al 2006), and lower than that in blue mussel Mytilus sp. (432 ng/g dry weight) collected from harbors in Arcachon Bay, France (Devier et al 2005). The results indicate that serious PAH contamination exists in foodstuff in the tested area, which might be likely originated from local large-scale e-waste recycling activities.…”
Section: Resultsmentioning
confidence: 81%